A Rare Case of Recurrent Myoid Hamartoma Mimicking Malignancy: Imaging Appearances - Ko, Myung-Su; Jung, Won Sang; Cha, Eun Suk; Choi, Hyun Joo (Korean journal of radiology, 2010)
Myoid hamartoma is an uncommon type of breast hamartoma and its recurrence is very rare. We report the imaging appearance of an unusual case of recurrent myoid hamartoma of the breast mimicking malignancy in a 43-year-old woman. Although the mammographic and ultrasonographic findings have long been described in the literature, MR finding with a dynamic study has not, to the best of our knowledge, been reported previously.